Technostress among Library Professionals: Possible Causes, Symptoms, Coping Strategies, and Future Proposals - Panda, Subhajit (Zenodo, 2020)
Technostress is the feeling of anxiety or mental pressure caused by working with multiple and rapidly changing computer systems and mediating between these systems and the demands of the organisation, users and personal life. This study investigated the nature and extent of technostress, the factors causing technostress, the effect of technostress on professional and social lives among the Library Professionals in India. The study further investigates the coping strategies to deal with technostress & also give a proposal of Positive Technology for technostress prevention and management. The study was carried through an online survey with a structured questionnaire designed on a Google form. Total of 500 respondents was selected for the study over four designated domain viz. Library Assistant, Assistant Librarian, Deputy Librarian and Librarian or University Librarian. Whereas 10 preferred causes and coping strategies, and 8 identified physiological & psychological symptoms are subjected in front of the library professionals to examine their preferability. The findings of the study may be used to develop strategies and policies which facilitate librarians to avoid, adapt to, or mitigate technostress. : {"references": ["Aghwotu, P. T., & Owajeme, O. J. (2010). Technostress: Causes, symptoms and coping strategies among librarians in university libraries. Educational Research, 1(12), 713-720.", "Ahmad, U. N. U., & Amin, S. M. (2012). The Dimensions of Technostress among Academic Librarians.\u00a0Procedia - Social and Behavioral Sciences,\u00a065, 266\u2013271. https://doi.org/10.1016/j.sbspro.2012.11.121", "Al-Qallaf, C. L. (2006). Librarians and Technology in Academic and Research Libraries in Kuwait: Perceptions and Effects.\u00a0Libri,\u00a056(3). https://doi.org/10.1515/libr.2006.168", "Arnetz, B. B., & Wiholm, C. (1997). Technological stress: Psychophysiological symptoms in modern offices.\u00a0Journal of Psychosomatic Research,\u00a043(1), 35\u201342. https://doi.org/10.1016/s0022-3999(97)00083-4", "Brillhart, P.E. (2004). Technostress in the Workplace: Managing Stress in the Electronic Workplace. Journal of American Academy of Business, Cambridge, 5, 302-307.", "Brivio, E., Gaudioso, F., Vergine, I., Mirizzi, C. R., Reina, C., Stellari, A., & Galimberti, C. (2018). Preventing Technostress Through Positive Technology.\u00a0Frontiers in Psychology,\u00a09. https://doi.org/10.3389/fpsyg.2018.02569", "Brod, C. (1984). Technostress: the human cost of the computer revolution. Addison-Wesley, Reading", "Calvo, R. A., & Peters, D. (2012). Positive computing.\u00a0Interactions,\u00a019(4), 28\u201331. https://doi.org/10.1145/2212877.2212886", "Dello Iacovo, L. (2012, March 31). Always connected? Volkswagen is not the only one that blocks emails to employees after 7pm. The other cases.\u00a0IlSole24ore. shorturl.at/bjDM6", "Gaudioso, F., Turel, O., & Galimberti, C. (2017). The mediating roles of strain facets and coping strategies in translating techno-stressors into adverse job outcomes.\u00a0Computers in Human Behavior,\u00a069, 189\u2013196. https://doi.org/10.1016/j.chb.2016.12.041", "Hsiao, K.-L. (2017). Compulsive mobile application usage and technostress: the role of personality traits.\u00a0Online Information Review,\u00a041(2), 272\u2013295. https://doi.org/10.1108/oir-03-2016-0091", "Jena, R. K., & Mahanti, P. K. (2014). An Empirical study of Technostress among Indian Academicians.\u00a0International Journal of Education and Learning,\u00a03(2), 1\u201310. https://doi.org/10.14257/ijel.2014.3.2.01", "Khasawneh, O. (2018, March). The Conceptual Gap Between Technophobia and Computer Anxiety and Its Empirical Consequences.\u00a0Global Information Technology Management (GITMA) World Conference. shorturl.at/frPXY", "Lazarus, R. S. (1966).\u00a0Psychological stress and the coping process.\u00a0McGraw-Hill, New York.", "Lazarus, Richard S, & Folkman, S. (1984).\u00a0Stress, appraisal, and coping. Springer, New York.", "Mark, G., Gudith, D., & Klocke, U. (2008). The Cost of Interrupted Work: More Speed and Stress.\u00a0Twenty-Sixth Annual CHI Conference on Human Factors in Computing Systems - CHI'08, 107\u2013110. shorturl.at/elAG1", "Ogada, H., Kwanya, T., & Kiplang'at, J. (2019). Technostress among Technical University Librarians in Kenya. In\u00a0Digital Technologies for Information and Knowledge Management. The Technical University of Kenya. shorturl.at/hiqzN", "Owolabi, S., Aregbesola, A., & Oyesola, O. (2015). Technostress, Library Staff and Productivity: Ray on Landmark University Library.\u00a0Journal of Applied Information Science and Technology,\u00a08(1), 9\u201315. https://www.jaistonline.org/vol8no1_2k15.html", "Pirkkalainen, H., Salo, M., Makkonen, M., & Tarafdar, M. (2017). Coping with Technostress: When Emotional Responses Fail.\u00a0Thirty Eighth International Conference on Information Systems, 1\u201317. https://www.researchgate.net/publication/332834923", "Ragu-Nathan, T. S., Tarafdar, M., Ragu-Nathan, B. S., & Tu, Q. (2008). The Consequences of Technostress for End Users in Organizations: Conceptual Development and Empirical Validation.\u00a0Information Systems Research,\u00a019(4), 417\u2013433. https://doi.org/10.1287/isre.1070.0165", "Riva, G., Ba\u00f1os, R. M., Botella, C., Wiederhold, B. K., & Gaggioli, A. (2012). Positive Technology: Using Interactive Technologies to Promote Positive Functioning.\u00a0Cyberpsychology, Behavior, and Social Networking,\u00a015(2), 69\u201377. https://doi.org/10.1089/cyber.2011.0139", "Riva, G., Gaggioli, A., Villani, D., Cipresso, P., Repetto, C., Serino, S., Triberti, S., Brivio, E., Galimberti, C., & Graffigna, G. (2014). Positive Technology for Healthy Living and Active Ageing. In G. Riva, P. A. Marsan, & C. Grassi (Eds.),\u00a0Active Ageing and Healthy Living\u00a0(pp. 44\u201356). IOS Press. http://ebooks.iospress.nl/publication/37278", "Sami, L. K., & Pangannaiah, N. B. (2006). \"Technostress\" A literature survey on the effect of information technology on library users.\u00a0Library Review,\u00a055(7), 429\u2013439. https://doi.org/10.1108/00242530610682146", "Seligman, M. E. P. (2002).\u00a0Authentic happiness\u202f: using the new positive psychology to realize your potential for lasting fulfilment. Atria Paperback, New York.", "Seligman, M. E. P., & Csikszentmihalyi, M. (2000). Positive psychology: An introduction.\u00a0American Psychologist,\u00a055(1), 5\u201314. https://doi.org/10.1037/0003-066x.55.1.5", "Tarafdar, M., Ragu-Nathan, B., Ragu-Nathan, T. and Tu, Q. (2005). Exploring the impact of technostress on productivity. In: Proceedings of the 36th annual meeting of the decision sciences institute, San Francisco", "Tarquini, A. (2014, February 16). BMW revolutionizes working hours: even emails and sms are counted.\u00a0La Repubblica. shorturl.at/yHK68", "Wang, K., Shu, Q., & Tu, Q. (2008). Technostress under different organizational environments: An empirical investigation.\u00a0Computers in Human Behavior,\u00a024(6), 3002\u20133013. https://doi.org/10.1016/j.chb.2008.05.007", "Weil, M. M., & Rosen, L. D. (1997).\u00a0TechnoStress\u202f: coping with technology @work @home @play. J. Wiley.", "Yuvaraj, M., & Singh, A. K. (2015). Effects and Measures of Technostress among Librarians in selected University Libraries of Delhi.\u00a0Library Philosophy and Practice (e-Journal),\u00a0Summer(1293). https://digitalcommons.unl.edu/libphilprac/1293/", "Clark, K. & Kalin, S. (1996). Technostressed out? How to cope in the digital age. Library Journal. 121(13), 30\u201332. https://eric.ed.gov/?id=EJ529677", "Davis-Millis, N. (1998). Technostress and the Organization - A Manager's Guide to Survival in the Information Age. https://web.mit.edu/ninadm/www/mla.htm", "DeLoughry, T. (1993). 2 researchers say \"Technophobia\" may affect millions of students. Chronicle of Higher Education. https://eric.ed.gov/?id=EJ462778", "Owusu-Ansah, S., Azasoo, J. Q., & Adu, I. N. (2016). Understanding the effects of techno-stress on the performance of banking staff. International Journal of Business Continuity and Risk Management, 6(3), 222\u2013236. https://doi.org/10.1504/IJBCRM.2016.079010", "Quinn, B. (2000). Overcoming Technostress in Reference Services to Adult Learners. The Reference Librarian, 33(69\u201370), 49\u201362. https://doi.org/10.1300/J120v33n69_05"]}